TRANSLATIONAL CONSTRUCTION OF AMERICAN CAPITALIST IDENTITY THROUGH RELIGIOUS TEXTS: CASE OF “DON’T FORGET THE SABBATH” AND “INGAT HARI SABAT” - Ntamwana, Simon; Adi, Ida Rochani (Pengkajian Amerika, Universitas Gadjah Mada, 2023)
This article investigates the construction of American capitalist identity by translating religious texts. Based on American Studies interdisciplinary method, the paper examines Crosby’s “Don’t Forget the Sabbath” and its Indonesian translation “Ingat Hari Sabat”. The focus of the study is to explore how and why the translation of the song lyric constructs American capitalist identity. The research is based on transnational American studies, poststructuralism, and Kristeva’s notions of revolt and nihilism. Schmidt’s model for conceptual metaphor (CM) translation and Kövecses’ notion of conceptual metaphor in American studies are employed. It is found that the rate of revolt is higher than that of nihilism in the translation. The revolt consists of the subversion of the American work ethic by resisting the concept of the Sabbath as a conduit into which capitalistic individualism is projected. Moreover, it is discovered that only the metaphors that manifest the concept of Sabbath as structure are annihilated because they reinforce evangelical and missionary traditions. The translation is, therefore, done to make American global evangelical Protestant culture fit the Indonesian local taste. Furthermore, it is found that Indonesian nihilism subdues the TT to another American national mythic narrative: manifest destiny.